If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + 48 = 48 Reorder the terms: 48 + 6w = 48 Add '-48' to each side of the equation. 48 + -48 + 6w = 48 + -48 Combine like terms: 48 + -48 = 0 0 + 6w = 48 + -48 6w = 48 + -48 Combine like terms: 48 + -48 = 0 6w = 0 Solving 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Divide each side by '6'. w = 0 Simplifying w = 0
| -20=-4-(6x) | | y=-2/3(-1)+1 | | y=-2/3(1)+1 | | 2u=-8 | | z-0.5=0.25z-0.125 | | U-9.9=4.99 | | y=-2/3(0)+1 | | 9(4x+8)=12(12+3x) | | h=-16t^2+1000 | | 32=6(x+4)-8x | | (3x+4)+(2x+2)= | | 8+5(7+5n)=193 | | 2.5x+1.96=1.7x+2.92 | | w+6-13=-27 | | 3(5x+4)=31 | | 3x+2(5)=0.2(2y+1) | | 45+5.50x=195+4.25x | | -x+3(-x+8)=0 | | 3+4+a=12 | | (C+5)+(c-1)=90 | | 4y+6(y+8)= | | 3(x+1)+4x=24 | | 18.1--0.7=c | | 75c^2+90cd+27d^2= | | 18.1--0.7= | | 16x^2-38x-5= | | 9=-7y+8 | | y=(3)(-1)-2 | | 79=8x-11 | | 5m-8.5=3.7m+4.37 | | 16x^2-38c-5= | | 2m^2-29m+60=0 |